ANALISIS LITERASI MATEMATIKA KONSEP BENTUK BANGUN DATAR PADA SISWA TUNAGRAHITA - Wayan Sukerti, Ni (Jurnal Pendidikan Khusus, 2016)
Abstract The achievement of learning mathematics result to mentally retardation students was still under standard determined. Mentally retardation students had difficulty in learning mathematics to analyze and formulate flat structure form. This reseach had purpose to analyze and formulate the concept of flat structure form to mentally retardation students by explaining, thickening, and drawing flat structure.  This reseach used descriptive method with qualitative approach. The data was collected using interview technique, structured observation, and documentation. Based on the reseach result, in explaining the flat structure comprehension the mentally retardation student had just been in thestep of showing the thingsas name, not the form. In formulating the flat structure form by thickening and drawing flat structure, the mentally retardation students had just been in the step of imitating the same flat structure form.         Keywords: mathematics literacy, flat structure.